Performance evaluation of free space optical link using OOK modulation schemes under dust-storm turbulence - Mohamed Rasied, Thaahirah Shireen; Hani Zailani, Nur Fazeera; Mohamad Sepian, Filzah Syafirah; almeslati, Muhamed; Habaebi, Mohamed Hadi; Basahel, Ahmed (IEEE, 2021)
Nowadays, free space optics (FSO) technology is one of the emerging technologies utilized as a complementary over radio frequency wireless technology with limited spectrum bandwidth to meet the high bandwidth demand. FSO technology fulfills the demands for massive bandwidth, faster data rate and low installation and maintenance cost. However, FSO transmission links for outdoor networks are vulnerable to atmospheric turbulence specifically in harsh weather conditions in which it deteriorates the performance of FSO systems. In this paper, a critical study on the performance of the FSO links in different dust storm conditions is presented. We aim to analyze the performance factors such as transmitted power control and link length that contribute to increase in signal-to-noise (SNR) ratio and bit-error-rate (BER) for On- Off Keying (OOK) modulation scheme. The results indicate that under low visibility, shorter link length performs better while increase in transmitted power contributes to small improvements. In contrast, at higher visibility, power control makes significant difference. A “9dbm” power increase over 1km link contributes 400m visibility improvement for OOK modulation. However, these visibility improvements will degrade proportionally as the link length is reduced.